Transformasi Kebijakan Moneter Islam dalam Menghadapi Digitalisasi Keuangan Global dan Stabilitas Ekonomi Nasional di Era Digital - Ramadhani, Annisa Dela; Ningsih, Ema Julia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the transformation of Islamic monetary policy in responding to global financial digitalization and its implications for national economic stability in the digital era. The rapid development of financial technology, digital payment systems, and the planned implementation of central bank digital currency have driven significant changes in the transmission mechanism of monetary policy, including within the framework of Islamic economics. This research employs a qualitative descriptive approach through a literature review of scientific journals, Bank Indonesia regulations, and reports from relevant institutions published since 2020. The findings indicate that Islamic monetary policy must adapt by strengthening sharia-based monetary instruments, integrating digital technology in accordance with Islamic principles, and enhancing the role of monetary authorities in maintaining financial system stability. Digitalization offers opportunities to improve efficiency, financial inclusion, and transparency, while also posing new risks such as financial volatility and unequal access to technology. Therefore, the transformation of Islamic monetary policy should be conducted in a measured and innovative manner, grounded in the values of justice and economic stability, to support national economic resilience amid global financial dynamics.